2009
DOI: 10.1002/jcp.21789
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Distribution of UCH‐L1 in Spermatogonia Is Associated With Maintenance and Differentiation of Spermatogonial Stem Cells

Abstract: Asymmetric division of germline stem cells in vertebrates was proposed a century ago; however, direct evidence for asymmetric division of mammalian spermatogonial stem cells (SSCs) has been scarce. Here, we report that ubiquitin carboxy-terminal hydrolase 1 (UCH-L1) is expressed in type A (As, Apr, and Aal) spermatogonia located at the basement membrane (BM) of seminiferous tubules at high and low levels, but not in differentiated germ cells distant from the BM. Asymmetric segregation of UCH-L1 was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 63 publications
5
84
0
Order By: Relevance
“…The isolation of this small spermatogonial population is technically challenging because of their small number, so magnetic beads are specifically useful for their isolation including stem cells from various tissues [23][24][25] and organ such as bone marrow, muscle and liver [26][27][28]. Many molecular markers have been used to identify and study undifferentiated spermatogonia and gonocytes such as promyelocytic leukemia zinc finger protein (PLZF) in rodents, non human primates and pigs [29][30][31][32], ubiquitin carboxyl esterase L1 (UCHL1) in the bull [33] and boar [32,34,35], VASA in many species including bulls [36], boars [37], primates [31] & mice [38], CD9 in mouse and rat [5]. The sorting efficiency of intact cells mainly rely on the availability of specific or particular surface markers on the membrane of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of this small spermatogonial population is technically challenging because of their small number, so magnetic beads are specifically useful for their isolation including stem cells from various tissues [23][24][25] and organ such as bone marrow, muscle and liver [26][27][28]. Many molecular markers have been used to identify and study undifferentiated spermatogonia and gonocytes such as promyelocytic leukemia zinc finger protein (PLZF) in rodents, non human primates and pigs [29][30][31][32], ubiquitin carboxyl esterase L1 (UCHL1) in the bull [33] and boar [32,34,35], VASA in many species including bulls [36], boars [37], primates [31] & mice [38], CD9 in mouse and rat [5]. The sorting efficiency of intact cells mainly rely on the availability of specific or particular surface markers on the membrane of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Markers for undifferentiated spermatogonia from piglets, UCHL1, PLZF [23] and THY1 [20], were expressed in the colonies. VASA, a marker of differentiating spermatogonia [22], was also expressed in the colonies (Fig. 4).…”
Section: Immunocytochemical Analysis Of Cultured Mgscsmentioning
confidence: 93%
“…Moreover, we have observed that mitotic gonocytes present daughter cells with different Gonocyte and spermatogonia differentiation R143 immunoreactions for a number of proteins, suggesting that gonocyte division is asymmetrical (Culty, unpublished data). Similarly, studies have shown that there is asymmetrical division in SSCs as well (Luo et al 2009). Further studies will be required to determine whether these differences correspond to cells with distinct fates and/or functions within the transitional gonocyte population.…”
Section: R142 G Manku and M Cultymentioning
confidence: 95%
“…Using SSEA1-FACS enrichment coupled to xenotransplantation assays, Kim et al (2013) proposed that SSEA1 is a marker of undifferentiated pig spermatogonia, including SSCs. Approximately half of SSEA1 enriched cells co-expressed Uchl1 (ubiquitin carboxyl-terminal esterase L1/PGP 9.5) and more than 40% expressed the undifferentiated spermatogonial marker PLZF, as well as VASA, considered as an SSC differentiation marker in boars (Luo et al 2009). In this model, Thy1, CD9, and a6-b1-integrins appeared less effective for spermatogonial enrichment than they are in rodent models, suggesting differences in SSC markers between porcine and rodent models.…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 99%